Elizabeth Fox: Intellectual Biography and History of a Field of Study - Heram, Yamila (2024)
The aim of this article is to highlight and recognize the contributions of one of the pioneers in Latin American communication studies, Elizabeth Fox, who since the late 1960s in Colombia has investigated media ownership and inequalities in the flow of information in the region. At the same time, the description of her intellectual journey reveals a transnational figure who established relations not only between different countries in the region but also with universities and agencies in the United States and Europe. In order to examine her trajectory, a meta-analysis of her academic publications serves to identify changes, ruptures, and continuities in her research topics and theoretical positions; an interview with the author was also conducted to complement the reconstruction of her trajectory. The main results and conclusions of the article are synthesized in a recovery of the critical traditions of the political economy of communication in her works published in the 1970s.